Recognition of Governments - Peterson, M. author. aut Link
IX, 295 p.
Keywords: Provides a systematic comparison of legal scholars' views and governments' practice regarding the occasions for, criteria for, and effects of recognition. It traces the evolution from the 19th century practice basing recognition mainly on effective rule to more frequent use of additional criteria in the interwar and early Cold War, to the reassertion of the primacy of effective rule since 1970 and places it in the context of contemporaneous changes in world politics.